2016
DOI: 10.1155/2016/7690632
|View full text |Cite
|
Sign up to set email alerts
|

Complications, Not Minimally Invasive Surgical Technique, Are Associated with Increased Cost after Esophagectomy

Abstract: Background. Minimally invasive esophagectomy (MIE) techniques offer similar oncological and surgical outcomes to open methods. The effects of MIE on hospital costs are not well documented. Methods. We reviewed the electronic records of patients who underwent esophagectomy at a single academic institution between January 2012 and December 2014. Esophagectomy techniques were grouped into open, hybrid, MIE, and transhiatal (THE) esophagectomy. Univariate and multivariate analyses were performed to assess the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Others found similar findings of lower overall cost at different time points, which were also attributed to decreased postoperative costs [98,99] . Conversely, Liu et al [100] compared MIE to OE and found that, even though the postoperative costs of MIE were significantly lower, this did not offset the higher procedural expense, as was found by other authors performing similar analyses [101][102][103] .…”
Section: Outcome Comparisons Of Open Minimally Invasive and Robotic-mentioning
confidence: 89%
“…Others found similar findings of lower overall cost at different time points, which were also attributed to decreased postoperative costs [98,99] . Conversely, Liu et al [100] compared MIE to OE and found that, even though the postoperative costs of MIE were significantly lower, this did not offset the higher procedural expense, as was found by other authors performing similar analyses [101][102][103] .…”
Section: Outcome Comparisons Of Open Minimally Invasive and Robotic-mentioning
confidence: 89%
“…Such a wide range of costs underscores the need for value-maximization approaches that reflect the spectrum of adverse outcomes associated with surgical oncology care. 27-32 Lacking this direction, well-intended interventions can easily go astray as has been demonstrated by the early surgical pay-for-performance complication-tracking established by Medicare and other partner organizations in 2006. The resultant program which targeted surgical site infections, venous thromboembolism, myocardial infarction, pneumonia, and catheter-associated urinary tract infections has been widely-criticized for overlooking important complications relevant to both elective 10,34 and emergent 8 indications and for focusing too much on urinary complications which minimally contributed to the overall cost of care.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, today, as the focus of surgical value-maximization begins to expand from its initial emphasis on colectomy and sub-specialty CABG and THA/TKA care to include a broader array of surgical procedures, 25,26 including those associated with surgical oncology, 27-32 research is needed in order to understand the impact of complications and guide the development of novel and adaptation of existing value-maximization approaches in meaningful ways. The objective of this study was to provide a framework to help achieve this end by comparing incremental costs of complications following major gastrointestinal (GI) resections for organ-specific malignant neoplasia using nationally-representative data.…”
Section: Introductionmentioning
confidence: 99%
“…Better recovery and faster social reinsertion may reduce the higher surgical costs of endoscopic surgical instruments, however, in order to reduce the duration of surgery, even in classic esophagectomy, mechanical devices are used to create faster the gastric conduit or to perform the intrathoracic anastomosis. Comparative studies in the literature did not report a difference in the real cost of MIE and had included postoperative complications, which are significantly associated factors of hospital costs also in open esophagectomy (9).…”
Section: Introductionmentioning
confidence: 99%